2022
DOI: 10.1177/07356331221087771
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Using Multimodal External Representations in Digital Game-Based Learning

Abstract: Although prior research has highlighted the significance of representations for mathematical learning, there is still a lack of research on how students use multimodal external representations (MERs) to solve mathematical tasks in digital game-based learning (DGBL) environments. This exploratory study was to examine the salient patterns problem solvers demonstrated using MERs when they engaged in a single-player, three-dimensional architecture game that requires the acquisition and application of math knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Consistent with other studies of GBL (Pan et al, 2022a; Sun et al, 2021), most studies in our meta-analysis were conducted with elementary and middle school students. The results indicated that the effect of GBL on CT was greater at the elementary school stage than at the middle school stage.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Consistent with other studies of GBL (Pan et al, 2022a; Sun et al, 2021), most studies in our meta-analysis were conducted with elementary and middle school students. The results indicated that the effect of GBL on CT was greater at the elementary school stage than at the middle school stage.…”
Section: Discussionmentioning
confidence: 65%
“…Computer and information science courses using GBL have a strong effect on students’ CT. On the one hand, the programming knowledge acquired in programming courses contributes to CT concept acquisition (Pellas & Vosinakis, 2018); on the other hand, when coding skills are applied in a GBL environment, it further enhances CT (Psycharis & Kallia, 2017). This could be because GBL transforms abstract concepts into concrete, visual objects and presents them in easy-to-understand learning contexts (Pan et al, 2022a), which can improve students’ cognition, skill, and affective learning outcomes. It is appropriate, therefore, to include GBL in CS courses to help develop CT.…”
Section: Discussionmentioning
confidence: 99%